Cancer Care and Control : South-South Knowledge Exchange - Schneidman, Miriam; Jeffers, Joanne; Duncan, Kalina (World Bank, Washington, DC, 2015)
Worldwide, deaths from cancer exceed those caused by human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS), tuberculosis, and malaria combined. Seventy percent of deaths due to cancer occur in low-and middle-income countries, which are often poorly prepared to deal with the growing burden of chronic disease. Over a period of 18 months, the cancer care and control South-South knowledge exchange brought together a group of stakeholders from five countries in Africa - Botswana, Kenya, Rwanda, Uganda, and Zambia to share experiences, lessons, and good practices through a set of video conferences and a site visit to Zambia. All five countries have demonstrated commitment, initiated various cancer control and cancer screening programs, and expressed interest in sharing their experiences. The knowledge exchange on cancer care and control aimed to raise awareness, increase knowledge of effective strategies, and strengthen regional collaboration in cancer control planning and expanding equitable access to cancer treatment. This paper presents highlights of the country experiences shared, common challenges discussed, and innovative solutions explored during the knowledge exchange. Topics addressed include population-based surveillance and data collection to better document the burden of cancer; strategies for designing and implementing successful national cancer care and control programs; innovative approaches for strengthening cancer prevention efforts such as human papilloma virus (HPV) vaccination programs; task sharing and other strategies to build capacity and increase access to services; analytical tools for understanding the costs of programs; financing models, including public private partnerships, to increase cancer prevention and care; policy reforms needed to improve access to palliative care; and opportunities for regional collaboration.